A porous single crystal sodium vanadium oxyfluorophosphate positive electrode material and its preparation method and application

By using polystyrene ball in situ growth and amorphous carbon coating technology in the positive electrode material of sodium vanadyl phosphate, a porous single crystal structure is formed, which solves the problems of small specific surface area and short cycle life of existing materials, and achieves high Power density and long cycle stability have expanded the application of sodium ion batteries in the fields of high power and long life.

CN115084474BActive Publication Date: 2024-12-13XI AN JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210776124.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-04
Publication Date
2024-12-13
Estimated Expiration
2042-07-04

AI Technical Summary

Technical Problem

The existing sodium vanadyl fluorophosphate composite cathode material has a small specific surface area, low electron conductivity and poor ion transport, resulting in limited application in the fields of high power and long life demand, and the material cycles prepared by the existing sol-gel method Short life span.

Method used

Polystyrene spheres were used as in-situ growth medium and template to synthesize porous single-crystalline vanadyl sodium fluorophosphate by hydrothermal method, and coated with amorphous carbon to form a structure to improve the specific surface area and electron conductivity of the material.

Benefits of technology

It significantly improves the specific capacity, rate performance and cycle life of the material, achieves high power density and long cycle stability, and meets the application needs of sodium ion batteries in the fields of high power and long life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003727399110000011
    Figure HDA0003727399110000011
  • Figure HDA0003727399110000012
    Figure HDA0003727399110000012
  • Figure HDA0003727399110000021
    Figure HDA0003727399110000021
Patent Text Reader

Abstract

The invention discloses a porous single crystal sodium vanadium oxyfluorophosphate positive electrode material and a preparation method and application thereof. A vanadium source and a carbon source are heated and reduced in a solvent, and then a sodium source, a phosphorus source and a fluorine source, as well as evenly dispersed polystyrene balls are added, and the mixture is stirred and mixed evenly. The sodium vanadium oxyfluorophosphate single crystal array obtained by hydrothermal reaction is annealed at 350 to 800° C. for 0.1 to 50 hours in an inert atmosphere to obtain an amorphous carbon-coated porous single crystal sodium vanadium oxyfluorophosphate positive electrode material. The amorphous carbon-coated porous single crystal structure strategy improves the power density and cycle life of the sodium vanadium oxyfluorophosphate, which is of great significance for the application of the material in sodium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sodium ion battery positive electrode materials, and in particular to a porous single crystal sodium vanadium oxyfluorophosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] Compared with lithium, sodium resources are abundant and cheap, so the research and development of sodium-ion batteries and related materials has become a hot spot for the new generation of energy storage devices. Since 2020, sodium-ion batteries have initially achieved commercial application, and have shown good application prospects in low-speed electric vehicles, tool vehicles, electric bicycles and large-scale energy storage with high cost-effectiveness requirements. Although sodium-ion batteries have the advantages of low price, high safety and long life, compared with lithium-ion batteries, the lower energy density and power density of sodium-ion batteries restrict the pace of their widespread application and the establishment of upstream and downstream industrial chains. As the most expensive material in the battery and the key material that determines the operating voltage of the battery, high-performance positive electrode sodium storage materials are the focus of current research. Among them, polyanionic phosphate positive electrode materials have become one of the best choices for sodium-ion battery positive electrode materials due to their stable crystal framework structure and easy adjustment of the material's discharge potential platform. Polyanionic sodium vanadium fluorophosphate positive electrode material has a stable three-dimensional open framework structure, which allows sodium ions to be reversibly deintercalated in three directions with little structural change, and has a high theoretical capacity (130mAhg -1 ) and high average operating voltage (~3.8V), making it a very promising cathode material for sodium-ion batteries.

[0003] However, the existing preparation methods of sodium vanadium fluorophosphate composite positive electrode materials, such as the sodium vanadium fluorophosphate composite positive electrode materials prepared by high-temperature solid phase method and carbon thermal reduction method, have a small specific surface area, which is not conducive to the infiltration of electrolyte, resulting in the sodium vanadium phosphate composite positive electrode material having unsatisfactory high current charge and discharge performance, and its rate performance is still difficult to meet the use requirements in some cases; although the material prepared by the sol-gel method has a large specific surface area and high power density, the material is crystalline and has many defects on the particle surface, resulting in a short cycle life. Therefore, the sodium vanadium fluorophosphate composite material prepared by the current method is difficult to reach a theoretical energy density of ~500Wh / kg and meet a higher power density due to many reasons such as low electronic conductivity, poor ion transmission, and poor crystallinity, which seriously affects the application pace of the material and sodium ion batteries in high power, long life and other demand fields. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention proposes a porous single crystal sodium vanadium oxyfluorophosphate positive electrode material and a preparation method and application thereof. The prepared positive electrode material has a high specific capacity, good rate performance and an ultra-long cycle life.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing a porous single crystal sodium vanadium oxyfluorophosphate positive electrode material comprises the following steps:

[0007] 1) adding colloidal polystyrene balls and a dispersant into ultrapure water, and using an ultrasonic instrument to uniformly disperse the polystyrene balls by high-energy ultrasonication;

[0008] 2) Take a sodium source, a vanadium source, a phosphorus source and a fluorine source according to the element ratio Na:V:P:F=3:2:2:x, and take a carbon source, wherein 1 <x<3;

[0009] 3) adding a vanadium source and a carbon source into ultrapure water to form a solution, heating the solution and stirring until the solution changes color to light green; then adding a sodium source, a fluorine source and a phosphorus source into the solution and continuing to stir and mix evenly to obtain a precursor solution;

[0010] 4) transferring the polystyrene sphere dispersion solution obtained in step 1) and the precursor solution obtained in step 3) to a hydrothermal reactor, heating the mixture to 120-200° C., keeping the temperature constant for 1 h to 50 h, and then naturally cooling the mixture to room temperature to obtain a porous single crystal sodium vanadium fluorophosphate precursor material;

[0011] 5) The porous single crystal sodium vanadium oxyfluorophosphate precursor material obtained in step 4) is heated to 300°C to 800°C at a heating rate of 2°C / min to 10°C / min under an inert atmosphere, kept at a constant temperature for 0.1h to 10h, and then naturally cooled to room temperature to obtain an amorphous carbon-coated porous single crystal sodium vanadium oxyfluorophosphate positive electrode material.

[0012] Furthermore, the size of the polystyrene spheres is 50-500 nm, and the dispersant is one or more of cetyltrimethylammonium bromide, sodium dodecyl sulfate, dopamine, sodium dodecylbenzene sulfonate and polyvinyl pyrrolidone.

[0013] Further, the vanadium source is one or more of ammonium metavanadate, vanadium pentoxide and vanadyl sulfate; the phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate and ammonium phosphate; the carbon source is oxalic acid (H 2 C 2 O 4 ·2H 2 O), malic acid (C 4 H 6 O 5 ) and citric acid (C 6 H 8 O 7 ·H 2O) in one or more, the carbon source content is 105% to 130% of the amount required to reduce pentavalent or tetravalent vanadium to trivalent vanadium, and the excess carbon source is used for in-situ carbon coating.

[0014] Furthermore, in step 3), the first stirring speed is 100-800 r / min, the stirring temperature is 40-100° C., and the stirring time is 0.1-6 h.

[0015] Furthermore, the sodium source is one or more of sodium fluoride, sodium chloride, sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium sulfate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate and sodium nitrate; the fluoride source is one or more of sodium fluoride, ammonium fluoride, potassium fluoride, lithium fluoride and magnesium fluoride.

[0016] Furthermore, in step 6), the inert atmosphere is one or both of argon and nitrogen.

[0017] A porous single crystal sodium vanadium oxyfluorophosphate positive electrode material, wherein the positive electrode material is an amorphous carbon-coated porous single crystal sodium vanadium oxyfluorophosphate structure.

[0018] Compared with the prior art, the present invention has the following beneficial technical effects:

[0019] In the present invention, polystyrene spheres are used as a medium and template for the in-situ growth of sodium vanadium fluorophosphate single crystals to form a porous single crystal structure. The porous single crystal structure coated with amorphous carbon can effectively improve the specific surface area, reaction active sites and power density of the material; the amorphous carbon coating is used as a medium for rapid electron conduction on the particle surface to improve the electronic conductivity and power density of the material; and the structural stability and cycle life of the material are improved by synthesizing single crystal particles.

[0020] 1) The single crystal sodium vanadium oxyfluorophosphate positive electrode material of the present invention has few defects, uniform particles, good structural stability and ultra-long cycle life.

[0021] 2) The present invention improves the electronic conductivity of the material through amorphous carbon coating, the three-dimensional porous structure promotes the infiltration and transmission of the electrolyte, and the porous single crystal structure increases the specific surface area of ​​the material and increases the active sites of the electrochemical reaction, which can greatly improve the power density of the composite positive electrode material; improve the specific capacity and good rate performance.

[0022] 3) The preparation method of the amorphous carbon-coated porous single crystal sodium vanadium fluorophosphate composite positive electrode material of the present invention has simple process and excellent performance, and can meet the requirements of electric bicycles, low-speed electric vehicles and other fields for fast charging and discharging and long cycle life, which is of great significance for the application of this material and sodium ion batteries in such fields.

[0023] The porous single crystal sodium vanadium oxyfluorophosphate positive electrode material prepared by the present invention conforms to the tetragonal crystal structure of sodium vanadium oxyfluorophosphate through X-ray diffraction testing, and the X-ray photoelectron spectrum also shows that amorphous carbon is successfully coated. Scanning electron microscope photos show that the pore structure on the surface of the single crystal material is evenly distributed. The electrochemical performance test results show that the cycle stability of the porous single crystal sodium vanadium oxyfluorophosphate is significantly improved and the rate performance is significantly enhanced. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a microscopic SEM image of the sample of Example 1 of the present invention;

[0025] Figure 2 The XRD pattern of the sample of Example 1 of the present invention;

[0026] Figure 3 This is a cycle performance diagram of the sample of Example 1 of the present invention;

[0027] Figure 4 It is a comparison diagram of the rate performance curves of Example 1 of the present invention and the comparative example sample. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0029] Example 1

[0030] 1) adding a certain amount of 100 nm colloidal polystyrene spheres and dispersant hexadecyltrimethylammonium bromide into a beaker of ultrapure water, and using an ultrasonic device to uniformly disperse the polystyrene spheres in the beaker by high-energy ultrasonication;

[0031] 2) taking a certain amount of sodium fluoride, vanadyl sulfate and ammonium dihydrogen phosphate according to Na:V:P:F=3:2:2:2.5, and taking oxalic acid as a carbon source;

[0032] 3) Add the vanadyl sulfate and oxalic acid in step 2) into a beaker of ultrapure water to form a solution, and heat and stir the solution until the solution changes color to light green. Add sodium fluoride and ammonium dihydrogen phosphate to the solution and continue stirring for 0.5h to obtain a uniformly mixed precursor solution;

[0033] 4) transferring the polystyrene ball dispersion solution in step 1) and the precursor solution in step 3) to a hydrothermal reactor, heating to 200° C., keeping the temperature constant for 5 hours, and then naturally cooling to room temperature to obtain a porous single crystal sodium vanadium fluorophosphate precursor material;

[0034] 5) heating the precursor material in step 4) to 600° C. at a heating rate of 5° C. / min under an argon atmosphere, keeping the temperature constant for 4 hours, and then naturally cooling to room temperature to obtain an amorphous carbon-coated porous single crystal sodium vanadium fluorophosphate positive electrode material;

[0035] Example 2

[0036] 1) Add a certain amount of 500 nm colloidal polystyrene spheres and dispersant sodium dodecyl sulfate into a beaker of ultrapure water, and use an ultrasonic device to uniformly disperse the polystyrene spheres in the beaker by high-energy ultrasonication;

[0037] 2) taking a certain amount of sodium chloride, ammonium metavanadate, ammonium dihydrogen phosphate and ammonium fluoride according to Na:V:P:F=3:2:2:2.8, and taking citric acid as a carbon source;

[0038] 3) Add the ammonium metavanadate and citric acid in step 2) to a beaker of ultrapure water to form a solution, and heat the solution and stir until the solution changes color to light green. Add sodium chloride, ammonium fluoride and diammonium dihydrogen phosphate to the solution and continue stirring for 0.5h to obtain a uniformly mixed precursor solution;

[0039] 4) transferring the polystyrene ball dispersion solution in step 1) and the precursor solution in step 3) to a hydrothermal reactor, heating to 180° C., keeping the temperature constant for 10 hours, and then naturally cooling to room temperature to obtain a porous single crystal sodium vanadium fluorophosphate precursor material;

[0040] 5) heating the precursor material in step 4) to 500° C. at a heating rate of 5° C. / min under a nitrogen atmosphere, keeping the temperature constant for 5 hours, and then naturally cooling to room temperature to obtain an amorphous carbon-coated porous single crystal sodium vanadium fluorophosphate positive electrode material;

[0041] Example 3

[0042] 1) adding a certain amount of 50 nm colloidal polystyrene spheres and dispersant sodium dodecylbenzene sulfonate into a beaker of ultrapure water, and using an ultrasonic device to uniformly disperse the polystyrene spheres in the beaker by high-energy ultrasonication;

[0043] 2) taking a certain amount of sodium bicarbonate, vanadyl sulfate, ammonium dihydrogen phosphate and lithium fluoride according to Na:V:P:F=3:2:2:2.8, and taking malic acid as a carbon source;

[0044] 3) Add the vanadyl sulfate and malic acid in step 2) to a beaker of ultrapure water to form a solution, heat the solution and stir until the solution changes to light green, with a stirring speed of 100 to 800 r / min, a stirring temperature of 40 to 100° C., and a stirring time of 0.1 to 6 h. Add lithium fluoride, sodium bicarbonate, and ammonium dihydrogen phosphate to the solution and continue stirring for 0.5 h to obtain a uniformly mixed precursor solution;

[0045] 4) transferring the polystyrene ball dispersion solution in step 1) and the precursor solution in step 3) to a hydrothermal reactor, heating to 200° C., keeping the temperature constant for 4 hours, and then naturally cooling to room temperature to obtain a porous single crystal sodium vanadium fluorophosphate precursor material;

[0046] 5) heating the precursor material in step 4) to 600° C. at a heating rate of 5° C. / min under a nitrogen atmosphere, keeping the temperature constant for 3 hours, and then naturally cooling to room temperature to obtain an amorphous carbon-coated porous single crystal sodium vanadium fluorophosphate positive electrode material;

[0047] Example 4

[0048] 1) Add a certain amount of 200 nm colloidal polystyrene spheres and dispersant polyvinyl pyrrolidone into a beaker of ultrapure water, and use an ultrasonic device to uniformly disperse the polystyrene spheres in the beaker by high-energy ultrasonication;

[0049] 2) taking a certain amount of sodium fluoride, ammonium metavanadate and diammonium hydrogen phosphate according to Na:V:P:F=3:2:2:2.5, and taking citric acid as a carbon source;

[0050] 3) Add the ammonium metavanadate and citric acid in step 2) to a beaker of ultrapure water to form a solution, and heat and stir the solution until the solution changes color to light green. Add sodium fluoride and diammonium hydrogen phosphate to the solution and continue stirring for 0.5h to obtain a uniformly mixed precursor solution;

[0051] 4) transferring the polystyrene ball dispersion solution in step 1) and the precursor solution in step 3) to a hydrothermal reactor, heating to 160° C., keeping the temperature constant for 10 hours, and then naturally cooling to room temperature to obtain a porous single crystal sodium vanadium fluorophosphate precursor material;

[0052] 5) heating the precursor material in step 4) to 600° C. at a heating rate of 5° C. / min under a nitrogen atmosphere, keeping the temperature constant for 5 hours, and then naturally cooling to room temperature to obtain an amorphous carbon-coated porous single crystal sodium vanadium fluorophosphate positive electrode material;

[0053] Comparative Example

[0054] 1) taking a certain amount of sodium fluoride, vanadyl sulfate and ammonium dihydrogen phosphate according to Na:V:P:F=3:2:2:2.5, and taking oxalic acid as a carbon source;

[0055] 2) Add the vanadyl sulfate and oxalic acid in step 1) into a beaker of ultrapure water to form a solution, and heat and stir the solution until the color of the solution changes to light green. Add sodium fluoride and ammonium dihydrogen phosphate to the solution and continue stirring for 0.5h to obtain a uniformly mixed precursor solution;

[0056] 3) transferring the precursor solution in step 2) to a hydrothermal reactor, heating it to 200° C., keeping the temperature constant for 5 hours, and then naturally cooling it to room temperature to obtain a porous single crystal sodium vanadium fluorophosphate precursor material;

[0057] 4) heating the precursor material in step 3) to 600° C. at a heating rate of 5° C. / min under a nitrogen atmosphere, keeping the temperature constant for 4 hours, and then naturally cooling to room temperature to obtain a sodium vanadium fluorophosphate positive electrode material;

[0058] The amorphous carbon-coated porous single crystal sodium vanadium fluorophosphate positive electrode material prepared in Example 1-4 was mixed with the conductive agent super P / carbon nanotubes and the binder CMC in a mass ratio of 7:2:1 and dissolved in ultrapure water. The slurry was scraped onto aluminum foil, dried and rolled, and then cut into pieces as the positive electrode, the metal sodium sheet as the negative electrode, and the glass fiber membrane as the separator. The solute was 1M NaPF 6 The solvent was a mixture of EC (ethylene carbonate) and DEC (diethyl carbonate) (mass ratio 1:1) as the electrolyte, and aluminum foil was used as the current collector to assemble a CR2025 button-type sodium-ion battery for electrochemical performance testing.

[0059] The performance test of the battery prepared above was carried out, and the test results are as follows:

[0060] Figure 1 This is a field emission scanning electron microscope (SEM) image of the porous single crystal sodium vanadium oxyfluorophosphate material prepared in Example 1, showing that the prepared material is micron-sized with evenly distributed pores on the surface.

[0061] Figure 2 The XRD patterns of the porous single crystal sodium vanadium oxyfluorophosphate material prepared in Example 1 and the sodium vanadium oxyfluorophosphate material prepared in the comparative example, the diffraction peaks of the two samples can correspond well to the standard JCPDS card (PDF#89-8485), which indicates that the formation of the porous structure will not change the overall crystalline phase of the sodium vanadium oxyfluorophosphate, and no impurity phase is generated during the synthesis.

[0062] Figure 3 The electrochemical performance curve of Example 1 shows that the prepared porous single crystal sodium vanadium oxyfluorophosphate material can maintain a reversible discharge capacity of about 109 mAh g-1 at a current density of 1C. After 350 cycles, the capacity retention rate is as high as 99.1%, and the coulombic efficiency is maintained at about 99.8%, indicating that the porous single crystal structure has excellent cycle stability. The attenuation of the material during the cycle can be as low as 2.5E-5 per cycle, which is almost negligible. The cycle life is expected to exceed 10,000 cycles.

[0063] Figure 4The rate performance curves of the electrochemical performance of Example 1 and the comparative example show that the reversible specific capacity of the prepared porous single crystal material is higher than that of the comparative example sample when the current density is greater than 2C. This indicates that the prepared porous material increases the specific surface area of ​​the material, expands the contact area between the material and the electrolyte, increases the reaction active sites, and improves the high rate performance of the material.

[0064] Example 5

[0065] 1) Add a certain amount of 200 nm colloidal polystyrene spheres and dispersant dopamine into a beaker of ultrapure water, and use an ultrasonic device to uniformly disperse the polystyrene spheres in the beaker by high-energy ultrasonication;

[0066] 2) taking a certain amount of sodium carbonate, vanadium pentoxide, phosphoric acid and potassium fluoride according to Na:V:P:F=3:2:2:1, and taking citric acid as a carbon source;

[0067] 3) Add the vanadium pentoxide and citric acid in step 2) to a beaker of ultrapure water to form a solution, and heat and stir the solution until the solution changes color to light green. Add sodium carbonate, phosphoric acid and potassium fluoride to the solution and continue stirring for 0.5h to obtain a uniformly mixed precursor solution;

[0068] 4) transferring the polystyrene ball dispersion solution in step 1) and the precursor solution in step 3) to a hydrothermal reactor, heating to 120° C., keeping the temperature constant for 50 hours, and then naturally cooling to room temperature to obtain a porous single crystal sodium vanadium fluorophosphate precursor material;

[0069] 5) heating the precursor material in step 4) to 800° C. at a heating rate of 2° C. / min under a nitrogen atmosphere, keeping the temperature constant for 0.1 h, and then naturally cooling to room temperature to obtain an amorphous carbon-coated porous single crystal sodium vanadium fluorophosphate positive electrode material;

[0070] Example 6

[0071] 1) Add a certain amount of 200 nm colloidal polystyrene spheres and dispersant polyvinyl pyrrolidone into a beaker of ultrapure water, and use an ultrasonic device to uniformly disperse the polystyrene spheres in the beaker by high-energy ultrasonication;

[0072] 2) taking a certain amount of sodium hydroxide, vanadium pentoxide, sodium dihydrogen phosphate and magnesium fluoride according to Na:V:P:F=3:2:2:3, and taking citric acid as a carbon source;

[0073] 3) Add the vanadium pentoxide and citric acid in step 2) to a beaker of ultrapure water to form a solution, heat the solution and stir until the solution changes color to light green. Add sodium hydroxide, sodium dihydrogen phosphate and magnesium fluoride to the solution and continue stirring for 0.5h to obtain a uniformly mixed precursor solution;

[0074] 4) transferring the polystyrene ball dispersion solution in step 1) and the precursor solution in step 3) to a hydrothermal reactor, heating to 200° C., keeping the temperature constant for 1 hour, and then naturally cooling to room temperature to obtain a porous single crystal sodium vanadium fluorophosphate precursor material;

[0075] 5) heating the precursor material in step 4) to 300° C. at a heating rate of 10° C. / min under a nitrogen atmosphere, keeping the temperature constant for 10 hours and then naturally cooling to room temperature to obtain an amorphous carbon-coated porous single crystal sodium vanadium fluorophosphate positive electrode material;

[0076] Example 7

[0077] The only difference from Example 6 is that the sodium source is one or more of sodium sulfate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate and sodium nitrate; and the phosphorus source is one or more of disodium hydrogen phosphate, sodium phosphate and ammonium phosphate.

[0078] In order to solve the problems of low power density and short cycle life of sodium vanadium oxyfluorophosphate, the present invention adopts a strategy of coating porous single crystals with amorphous carbon, synthesizes through hydrothermal and high-temperature annealing, improves the electronic conductivity, specific surface area and reaction active sites of the material, effectively improves the power density and cycle stability of the material, and adopts in-situ carbon coating, particle porosity and single crystallization to improve the sodium storage performance of the material, which is of great significance to the expansion of the application field of sodium vanadium oxyfluorophosphate and sodium ion batteries.

Claims

1. A method for preparing a porous single crystal sodium vanadium oxyfluorophosphate positive electrode material, characterized in that The following steps are involved: 1) adding colloidal polystyrene balls and a dispersant into ultrapure water, and using an ultrasonic instrument to uniformly disperse the polystyrene balls by high-energy ultrasonication; the dispersant is one or more of cetyltrimethylammonium bromide, sodium dodecyl sulfate, dopamine, sodium dodecylbenzene sulfonate and polyvinyl pyrrolidone; 2) Take sodium source, vanadium source, phosphorus source and fluorine source according to the element ratio Na: V: P: F = 3:2:2:x, and take carbon source, where 1 <x<3; 3) adding a vanadium source and a carbon source into ultrapure water to form a solution, heating the solution and stirring the solution until the solution changes color to light green; then adding a sodium source, a fluorine source and a phosphorus source into the solution and continuing to stir and mix evenly to obtain a precursor solution; 4) transferring the polystyrene sphere dispersion solution obtained in step 1) and the precursor solution obtained in step 3) to a hydrothermal reactor, heating the mixture to 120 to 200°C, maintaining the temperature for 1 to 50 hours, and then naturally cooling the mixture to room temperature to obtain a porous single crystal sodium vanadium fluorophosphate precursor material; 5) The porous single crystal sodium vanadium oxyfluorophosphate precursor material obtained in step 4) is heated to 300°C to 800°C at a heating rate of 2°C / min to 10°C / min under an inert atmosphere, kept at a constant temperature for 0.1 h to 10 h, and then naturally cooled to room temperature to obtain an amorphous carbon-coated porous single crystal sodium vanadium oxyfluorophosphate positive electrode material.

2. The method for preparing the porous single crystal sodium vanadium oxyfluorophosphate positive electrode material according to claim 1, characterized in that: The polystyrene spheres have a size of 50-500 nm.

3. The method for preparing the porous single crystal sodium vanadium oxyfluorophosphate positive electrode material according to claim 1, characterized in that: The vanadium source is one or more of ammonium metavanadate, vanadium pentoxide and vanadyl sulfate; the phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate and ammonium phosphate; the carbon source is one or more of oxalic acid (H2C2O4·2H2O), malic acid (C4H6O5) and citric acid (C6H8O7·H2O), the carbon source content is 105%~130% of the amount required to reduce pentavalent or tetravalent vanadium to trivalent vanadium, and the excess carbon source is used for in-situ carbon coating.

4. The method for preparing the porous single crystal sodium vanadium oxyfluorophosphate positive electrode material according to claim 1, characterized in that: In the step 3), the first stirring speed is 100 to 800 r / min, the stirring temperature is 40 to 100 ºC, and the stirring time is 0.1 to 6 h.

5. The method for preparing the porous single crystal sodium vanadium oxyfluorophosphate positive electrode material according to claim 1, characterized in that: The sodium source is one or more of sodium fluoride, sodium chloride, sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium sulfate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate and sodium nitrate; the fluoride source is one or more of sodium fluoride, ammonium fluoride, potassium fluoride, lithium fluoride and magnesium fluoride.

6. The method for preparing the porous single crystal sodium vanadium oxyfluorophosphate positive electrode material according to claim 1, characterized in that: In step 5), the inert atmosphere is one or both of argon and nitrogen.

7. A porous single crystal sodium vanadium oxyfluorophosphate positive electrode material prepared according to the preparation method according to any one of claims 1 to 6.

8. The porous single crystal sodium vanadium oxyfluorophosphate positive electrode material according to claim 7, characterized in that: The positive electrode material is an amorphous carbon-coated porous single-crystalline sodium vanadium fluorophosphate structure.

9. Use of the porous single crystal sodium vanadium oxyfluorophosphate positive electrode material as claimed in claim 8 in a sodium ion battery.